Little Christmas dream with MDAS promotional campaign for Muscular Dystrophy Association (Singapore). - Loo, Carol May San. (2008)
Muscular dystrophy (MD) is a disease that is little known in Singapore. In 2000, the Muscular Dystrophy Association of Singapore (MDAS) was set up with the aim to provide care and support to MD patients and their family members. However, since its establishment, MDAS has not undertaken any major publicity effort to promote its cause, and has faced problems with obtaining monetary support for its activities, as well as a shortage in manpower.